Chalcogen bonding macrocycles and [2]rotaxanes for anion recognition - Lim, J; Marques, I; Thompson, A; Christensen, K; Felix, V; Beer, P (American Chemical Society, 2017)
Electron-deficient heavy chalcogen atoms contain Lewis acidic σ-holes which are able to form attractive supramolecular interactions, known as chalcogen bonding (ChB), with Lewis bases. However, their potential in solution-phase anion binding applications is only just beginning to be realized in simple acyclic systems. Herein, we explore the 5-(methylchalcogeno)-1,2,3-triazole (chalcogen = Se, Te) motif as a novel ChB donor for anion binding. Other than being chemically robust enough to be incorporated into macrocyclic structures, thereby significantly expanding the scope and complexity of ChB host systems, we also demonstrate, by 1H NMR and DFT calculations, that the chalcogen atoms oriented within the macrocycle cavity are able to chelate copper(I) endotopically. Exploiting this property, the first examples of mechanically interlocked [2]rotaxanes containing ChB-donor groups are prepared via an active metal template strategy. Solution-phase 1H NMR and molecular modeling studies provide compelling evidence for the dominant influence of ChB in anion binding by these interlocked host systems. In addition, unprecedented charge-assisted ChB-mediated anion binding was also studied in aqueous solvent mixtures, which revealed considerable differences in anion recognition behavior in comparison with chalcogen-free host analogues. Moreover, DFT calculations and molecular dynamics simulations in aqueous solvent mixtures indicate that the selectivity is determined by the different hydrophilic characters of the anions allied to the hydration of the binding units in the presence of the anions. Exploiting the NMR-active nuclei of the ChB-donor chalcogen atoms, heteronuclear 77Se and 125Te NMR were used to directly study how anion recognition influences the local electronic environment of the chalcogen atoms in the mechanically bonded rotaxane binding sites in organic and aqueous solvent mixtures.